The Prophetic Mud Standard: A Comprehensive Jurisprudential, Socio-Technical, and Ecological Critique of Water Extravagance in Ritual Purification - Harsing Harsing; Irfan Alkhotiri; Agus Salim (STAI Minhajul Haq, 2026)
Ritual purification (Wudu) is a fundamental Islamic practice, yet contemporary implementation often results in significant water waste (Israf). This study analyzes the Prophetic benchmark of one Mud—approximately 600 to 775 ml—against modern consumption patterns in mosques. Using a mixed-methods approach, including historical metrological analysis and a review of empirical data from Indonesian mosques, the research identifies a socio-technical mismatch between traditional values and modern plumbing systems. Findings indicate that modern practitioners consume between 2.47 and 7 liters per Wudu, representing a 300% to 1100% deviation from the Sunnah. The study proposes a synergistic model combining technical interventions, such as Water-Efficient Aerators (WEAs) and